Wars of the Realm: Cloak of the Light - Book 1 - Black, Chuck (Colorado Springs, Colorado : Multnomah Books, 2014)
Since the age of twelve when his father died, Drew has been mentored by one of his father's friends from Special Forces, and he must put his skills to use a few years later when he becomes involved in a war between realms.
Keywords: Adventure and adventurers -- Fiction; Good and evil -- Fiction; Angels -- Fiction; Christian life -- Fiction; Single-parent families -- Fiction; Family life -- Fiction -- South Carolina; Adventure stories; Good and evil -- Juvenile fiction; Angels -- Juvenile fiction; Christian life -- Juvenile fiction; Single-parent families -- Juvenile fiction; Families -- Juvenile fiction -- South Carolina; JUVENILE FICTION / Religious / Christian / Action & Adventure; JUVENILE FICTION / Action & Adventure / General; JUVENILE FICTION / Religious / Christian / Fantasy